Genome-wide DNA binding pattern of the homeodomain transcription factor Sine oculis (So) in the developing eye of Drosophila melanogaster - Barbara Jusiak; Feng Wang; Umesh C. Karandikar; Su-Jin Kwak; Hui Wang; Rui Chen; Graeme Mardon (Genomics Data, 2014)
The eye of the fruit fly Drosophila melanogaster provides a highly tractable genetic model system for the study of animal development, and many genes that regulate Drosophila eye formation have homologs implicated in human development and disease. Among these is the homeobox gene sine oculis (so), which encodes a homeodomain transcription factor (TF) that is both necessary for eye development and sufficient to reprogram a subset of cells outside the normal eye field toward an eye fate. We have performed a genome-wide analysis of So binding to DNA prepared from developing Drosophila eye tissue in order to identify candidate direct targets of So-mediated transcriptional regulation, as described in our recent article [20]. The data are available from NCBI Gene Expression Omnibus (GEO) with the accession number GSE52943. Here we describe the methods, data analysis, and quality control of our So ChIP-seq dataset.